Uknowhatimsayin¿ [compact disc] - Brown, Danny, 1981- (Warp Records, 2019)
The album marks a buoyant new chapter in Brown's career, a transitional and celebratory moment. His profile has grown since Atrocity and now armed with a cable TV show, and a co-sign from one of rap's icons, he will look to solidify his positioning as a ubiquitous entertainer, independent rap hero, and one of the essential cultural voices of this era, while still retaining the edgy, maverick style that makes him a fan-favorite.